Zum Wesen der Übersetzungseinheit - Jopkiewicz, Katarzyna (Wydawnictwo Naukowe UAM, 2013)
The questions of a translation unit, its dimensions and natural features have absorbed the traductologists since the origins of translatology. According to this, the primary purpose of this paper is to establish the range of the most important defining propositions and further to consider the issue, whether a translation unit should be in fact understood as a word, a phrase, a sentence, a text, culture or a variable entity. The approach will put forward the claim that it is necessary to differentiate between the unit of translation and the unit of translating, and that the appropriate text type particularly determines the dimensions of the unit of translating.
On the Essence of a Translation Unit
Keywords: the unit of translation; the unit of translating